The indeclinable relativizer što - an analysis of examples from contemporary spoken Croatian - Polančec, Jurica; Gnjatović, Tena (2014)
The most common relativizer in Croatian is the relative pronoun koji, koja, koje 'who, which', e.g. Zaposlite učitelja kojeg djeca poznaju ‘Hire the teacher that the children know’. In some contexts koji can be replaced with the indeclinable relativizer što, accompanied by a resumptive pronoun, except in the case of subject relative clauses. Što is frequently described in grammars as a characteristic of literary style, and is typically perceived as such by native Croatian speakers as well. However, our analysis of informal language used in spontaneous speech and on internet blogs and forums shows that što and its substandard variants šta, kaj and ča are actually very common in spoken language as a substitute for the default relativizer koji. Moreover, we noticed a tendency to omit the resumptive pronoun in relative clauses introduced by što/šta/kaj/ča, especially if it functions as the direct object, but also when it is part of an adverbial prepositional phrase. The structure of the relative clause is thus simplified, resulting in a higher resemblance to other subordinate clauses in Croatian.
ENG